Transient diabetes insipidus following Escherichia coli meningitis complicated by ventriculoperitoneal shunt - Kabakus, N; Yilmaz, B; Aydinoglu, H; Serhathoglu, S (Editrice Kurtis S R L, 1999)
Although disorders of ADH secretion associated with meningitis are usually consistent with the Syndrome of Inappropriate Antidiuretic Hormone Secretion (SIADH), central diabetes insipidus (DI) is an exceptional complication of meningitis. Transient DI as a complication of Escherichia coli (E. coli) meningitis due to ventriculoperitoneal shunt in an 18-month-old boy is presented. Blood and spinal fluid cultures yielded E. coli, sensitive to cefotaxime. The DI arose on the day 3 after admission and continued to the day 20. Treatment comprised cefotaxime, dexamethasone, fluid adjustment and vasopressin. The course of our case supports that in cases of bacterial meningitis, initial fluid restriction may occasionally result in dangerous conditions. Therefore, all children with bacterial meningitis should be followed closely not only in terms of SIADH but also DI. To our knowledge this is the first transient DI associated with E. coli-caused meningitis case reported. (J. Endocrinol. Invest. 21: 800-802, 1999) (C)1999, Editrice Kurtis.
Keywords: diabetes insipidus; SIADH; vasopressin; meningitis; children